Pengaruh Kompensasi, Lingkungan Kerja dan Motivasi Kerja terhadap Kinerja Karyawan PT BPRS Sukowati Sragen - Arviyanti, Della; Widyaningsih, Meilana (Masoem University, 2025)
This study to determine the influence of compensation, work environment and work motivation on the performance of employees of PT BPRS Sukowati Sragen. The method used for this research is a quantitative method with saturated sampling. The number of population and sampel in this study is 90 employees of PT BPRS Sukowati Sragen. Primary data for this study was collected by distributing quetionnaires to all employees of PT BPRS Sukowati Sragen. The data processing of this study uses SPSS 23.0. The result of this study are: 1) Compentation has a significant positive effect on the performance of PT BPRS Sukowati Sragen employees with a sig. < 0,05 (0,000 < 0,05) ; 2) The work environment has a significant positive effect on the performance of PT BPRS Sukowati Sragen employees with a sig. < 0,05 (0,001< 0,05) ; 3) Work motivation has a significant positive effect on employee performance with the calculation of sig.< 0,05 (0,038 < 0,05). Meanwhile, based on the result of the F test, the three variables have a simultaneous effect with F calculation (23,475) > F table (2,71) on the performance of PT BPRS Sukowati Sragen employees.